The enigmatic world of ancient graffiti : rock art in Chukotka : the Chaunskaya Region, Russia - Kirʹi͡ak, M. A. (Archaeopress archaeology., 2015)
This monograph is devoted to small forms of engraving on stone. It summarizes the archaeological material obtained during the course of excavations at the Rauchuvagytgyn I site (dated to 2500 years ago) in northern Chukotka. The book analyzes the content and semantics of the pictorial resources, and ethnic identification is made.